Slam surdo : uma análise das dimensões políticas e poéticas de performances de Edinho Santos e Gabriela Grigolom da Silva - Araújo, Wanderlina Maria de Souza (2020)
The recognition of the legal order of the Brazilian Sign Language – BSL or Libras in 2002, as well as its regulation in 2005, constituted a milestone in the lives of the deaf in Brazil because this population began to become more visible to other Brazilians including account of the way that language is implemented. Despite this elevation of linguistic status its use is still very restricted as well as the knowledge that one has. As we turn our attention to the literary area of Libras specifically on the production itself, the localization of texts in graphic support, related to the literature of the deaf becomes an arduous task because these are scarce. Which is why when we come across videos made available in the electronic media containing deaf people performing their own poems in sign languages, an academic curiosity motivated us to start another process of scientific research to understand this cultural phenomenology mainly because it occurs set in the so-called poetry slam or batalhas de poesia, originated in the United States and brought to Brazil in 2008, by Roberta Estrela D'Alva. A relatively recent artistic- literary manifestation. A modality that combines the dynamics of the ancient soirees with those characteristics of a competition. A spects detected supported an analogy with oral poetry according to Zumthor's assumptions. The finding of the approach of politically engaged themes pauted a theoretical foundation in Marcuse. Given the competitive characteristics of these slams in which the performance assumes relevance because it gains those who sensitize a jury randomly chosen from the audience during the presentation of the authorpoems, we based the study of these performances in Zumthor, Nunes and Schiffler. Ribeiro provided references to formal aspects of deaf poetry. For this study we selected four poems by two Brazilian deaf slammers: Gabriela Grigolom da Silva, from Curitiba and Edinho Santos, from São Paulo. We did not use any specific software because we did not object if we analyzed formal aspects of the poems primarily, but performative aspects of the actors, a factor that immediately monopolizes the attention of the public. Finally, we conclude that the work has brought both a view to slams in general how much greater knowledge about deaf peoples, their history, culture and literature; that there are still scientific reference gaps for poetry slam in the area of Libras/deafness; that performance aspects are also predominant in Libras in this type of artistic- cultural manifestation and are configured as differentiators of Libras of daily use from that of poetic performance, typical of these events, besides being evidenced, in slams, a lot of poetic creativity in this language; that in the poetry slams deaf with interpreter the process of cultural hybridization, according to Canclini, is more pronounced among speakers of Libras and the Portuguese language; whereas a Deaf Culture is effectively configured by cultural productions notably by the poems of the batalhas de poesia/poetry slams; finally, the slams of deaf poetry have a great impact on the communities of listeners conforming a new locus of resistance and diverse claims, revealing themselves by the performances a political dimension of great strength.